Differentiated instruction based on multiple intelligences as promising joyful and meaningful learning - Subuh Anggoro; Azmi Fitriati; Ng Khar Thoe; Corrienna Abdul Talib; Lia Mareza (International Journal of Evaluation and Research in Education (IJERE), 2024)
Boredom has previously been linked to negative academic outcomes such as academic motivation, strategies, and achievement. The understanding of multiple intelligence approaches creates opportunities for all learners to develop their potential to optimize learning through differentiated instructions. This research aims: i) to design and to develop differentiated instruction based on learners’ multiple intelligences for elementary schools; and ii) to measure the effectivity of students’ learning attitude and mastery of concepts. Using design and development research (DDR) anchored on analysis, development, design, implementation, and evaluation (ADDIE) model and quasi-experimental research, the differentiated instruction based on multiple intelligence was conducted in a private Islamic Elementary School in collaboration with 3 class teachers. Based on the results of observations conducted at the school, the findings revealed that the learners can maximize their logical-mathematical, language, kinesthetic, interpersonal, and intrapersonal intelligences through a differentiated instruction based on multiple intelligence approach. Students experienced a joyful and meaningful learning atmosphere; hence it was expected that their intelligences can be developed naturally. In addition. this instruction was found to be effective to enhance science concept mastery especially in the aspects of remembering, understanding, and applying. The differentiated instruction based on multiple intelligences should be developed further to examine the effectiveness of the model in thematic learning for students both with low and high achievement.